Electrophysiological mechanisms of action of ethmozine that explain its antiarrhythmic efficacy in the late stage of experimental myocardial infarction in dogs - Aidonidis, Isaac; Egel, Eva-Susanne; Hilbel, Thomas; Rizos, Ioannis-Antonios; Kübler, Wolfgang; Brachmann, Johannes (European heart journal, 1994)
The effects of intravenous ethmozine (3 mg. kg−1) on electrophysiological parameters of ischaemically damaged myocardium and induced ventricular tachyarrhythmias were studied by programmed stimulation in 17 conscious dogs with 4 to 8 day-old ligation of the left anterior descending coronary artery. Ethmozine showed a beneficial effect on sustained ventricular tachycardia by suppressing its inducibility in five of 14 animals or by slowing its rate in six of 14 animals. Ethmozine prolonged the ventricular effective refractory period in normal and infarcted myocardium, and impaired depressed conduction in ischaemically damaged tissue. The latter was indicated by significant lengthening of late potentials recorded from the infarction zone. The QT interval was only slightly increased with ethmozine. Our findings indicate an antiarrhythmic action of ethmozine in the late stage of myocardial infarction. Major mechanisms accounting for its efficacy may predominantly be associated with marked depression of slow conduction in the infarction zone, as well as with prolongation of ventricular refractoriness without significant changes of verticular repolarization.
Gesehen am 22.05.2024